The Reality of Promoting Citizenship Values in the Secondary School Curriculum in the Palestinian Territories - دلول, أحمد فايق (Milev Journal of Research and Studies, 2020)
The study aimed to identify the reality of citizenship in the curriculum of the secondary stage in the Palestinian territories. The two researchers were exposed to the concept of citizenship, its importance, dimensions and values. In addition, the reality of the secondary education stage in the Palestinian territories, and finally; Content analysis of some courses was conducted to explore where citizenship is. The researchers used the descriptive analytical method and the theory of content analysis. The main question of the study came as follows: What is the reality of promoting the values of active citizenship in the curriculum of the second stage in the Palestinian territories? The two researchers have reached a set of results; the most important of which is that the curriculum attempted to contribute to strength the values of citizenship, but their contribution - it seems - was not in a way that suits the size of the surrounding developments. Else, the study recommended to focus on specific values related to political developments in the Palestinian territories, such as: National unity, tolerance, civilization and solidarity.